INCOME OPTIMIZATION OF SMALLHOLDER RUBBER FARMING - Fitriana, Widya; Febriamansyah, Rudi; Mutiara, Vonny Indah (Fakultas Pertanian, Universitas Janabadra, 2024)
South Sumatra Province is the largest rubber producer in Indonesia, with a production share of 29 percent of the total national rubber production. However, since 2018, rubber production has tended to decline. This condition has an impact on the low contribution of rubber to GDP and reduces the income of rubber farmers. This study aims to (1) analyze the production and income of smallholder rubber farmers and (2) analyze the optimal income of smallholder rubber farmers. The study was conducted in Musi Rawas Utara District by interviewing 100 samples of smallholder rubber farmers using a simple random method. The variables observed include the amount of rubber production, rubber prices, rubber farming costs, total revenues, and total farm income, and then analyzed with optimization models. The results showed that the average production of smallholder rubber farming was 1,651 kg / Ha, lower than the optimal production of 4,840 kg / Ha. The income received by rubber farmers is Rp 14,164,390.2 /Ha/year, lower than the income of smallholder rubber farmers in Paser, East Kalimantan, but already higher than the income of rubber farmers in Simalungun, Sumatera Utara. To achieve an optimal income of IDR 24,784,438 / Ha/year, farmers are advised to rejuvenate because the rubber plants production is over 20 years. Farmers must use high-yielding rubber varieties and efficiently use other production inputs. The quality of processed rubber must also be improved to get a high selling price. Keywords : Rubber, Income, Optimization, Rubber, Smallholder farming, INTISARIProvinsi Sumatera Selatan merupakan produsen karet terbesar di Indonesia dengan pangsa produksi sebesar 29 persen dari total produksi karet nasional. Namun sejak tahun 2018, produksi karet cenderung menurun. Kondisi ini berdampak pada rendahnya kontribusi karet terhadap PDB dan menurunkan pendapatan petani karet. Penelitian ini bertujuan untuk (1) menganalisis produksi dan pendapatan petani karet rakyat dan (2) menganalisis pendapatan optimal petani karet rakyat. Penelitian dilakukan di Kabupaten Musi Rawas Utara dengan mewawancarai 100 sampel petani karet rakyat dengan menggunakan metode acak sederhana. Variabel yang diamati meliputi jumlah produksi karet, harga karet, biaya usahatani karet, total pendapatan, dan total pendapatan usahatani, kemudian dianalisis dengan model optimasi. Hasil penelitian menunjukkan bahwa rata-rata produksi usahatani karet rakyat sebesar 1.651 kg/Ha, lebih rendah dari produksi optimal sebesar 4.840 kg/Ha. Pendapatan yang diterima petani karet sebesar Rp 14.164.390,2 /Ha/tahun, lebih rendah dibandingkan pendapatan petani karet rakyat di Paser Kalimantan Timur, namun sudah lebih tinggi dibandingkan pendapatan petani karet di Simalungun, Sumatera Utara. Untuk mencapai pendapatan optimal sebesar Rp 24.784.438/Ha/tahun, petani disarankan melakukan peremajaan karena produksi tanaman karet sudah diatas 20 tahun. Petani harus menggunakan varietas karet yang mempunyai produktivitas tinggi dan menggunakan input produksi lainnya secara efisien. Kualitas karet olahan juga harus ditingkatkan agar mendapatkan harga jual yang tinggi. Kata Kunci : Karet, Pendapatan, Optimasi, Karet, Usahatani Rakyat